The effect of the addition of Carboxymethyl Cellulose (CMC) on the formulation of batters on Coating Pick up and Frying Loss fried battered Tempeh - Hanif Muchdatul Ayunda; Safrida Safrida; Afwa Hayuningtyas (Universitas Teuku Umar, 2021)
One of the fried food processed products that are often found in roadside fried sellers is tempeh. This study aims to study the effect of CMC addition on the results of coating pick-up dan frying loss of fried battered tempeh. Hydrocolloids used were carboxyl methylcellulose (CMC) and pectin with concentrations of addition to the batter as much as 0.3%, 0.5%, 1% of the overall weight of the mixture. Temperature and tempeh frying time is at a temperature of 180oC and for 6 minutes. The results showed fried battered tempeh with the addition of CMC to its batters has good quality measured from the percentage of coating pick-up samples.